The principle of maṣlaḥah and its application in Islamic banking operations in Malaysia - Muhammad Shahrul Ifwat Ishak (ISRA International Journal of Islamic Finance, 2019)
Purpose: This paper aims to investigate the extent to which maslhah (public interest) is taken into consideration in Islamic banking operations in Malaysia, particularly in bayʿ al-ʿīnah (sale and buyback), taʿwid(compensation) and ibraʾ (rebate). Design/methodology/approach - This study applies deductive and inductive methods to analyze the application of maslahah in Islamic financial transactions. Three issues in Malaysia are selected as a case study, allowing bayʿ al-ʿīnah, standardizing the rate of taʿwi d and stipulating the ibraʾ clause in financial agreements. As this study is qualitative in nature, all data are analyzed based on the content analysis method. Findings - Both the maslahah of Islamic banks and their customers were found to be considered by the Central Bank of Malaysia in the implementation of contracts and principles of Islamic banking. The first maslahah represents the viability of Islamic banks, while the second maslahah promotes fairness and transparency between Islamic banks and their customers. Research limitations/implications - This study only focuses on the contracts and principles of Islamic banking operations in Malaysia with regard to three selected issues. Practical implications - This paper clarifies the practical application of maslahah in the Islamic banking industry, particularly with regard to implementing its contracts and principles. Originality/value - This paper analyzes the argument of maslahah on the issues of bayʿ al-ʿīnah , taʿwi d and ibraʾ in Malaysia, which are considered among scholars to be debatable issues. While many discussions focus on the legal aspect of Sharīʿah on those issues, this study emphasizes how the application of maslahah aims to solve the current problems and harmonize between Sharīʿah and reality.
Keywords: 330; Islamic banking; Bayʿ al-ʿīnah; Ibrāʿ; Maṣlaḥah; Taʿwid